2014
DOI: 10.1007/s00572-013-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungus diversity and community structure with natural and cultivated truffle hosts: applying lessons learned to future truffle culture

Abstract: Since the first truffle plantations were established in France, Italy and other parts in the world, many studies have been carried out to improve their productivity and sustainability. Success of plantations is clearly related to the mycorrhizal status of the host trees over the years, from inoculated seedlings to truffle-producing trees. The experience gained in monitoring the ectomycorrhizal fungus status in cultivated truffle grounds has allowed us to develop an extensive catalogue of the ectomycorrhizal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…The microbial community structures have been found to differ between natural and cultivated truffle habitats, between productive and nonproductive plantations, and between different Tuber species and developmental stages of truffles. Belfiori et al (2012) found that the diversity of ectomycorrhizal species is lower in cultivated plantations than in natural habitats, higher in Tuber brumale -colonized plants than that of T. melanosporum -colonized plants (Belfiori et al 2012), and higher in productive plantations than in the nonproductive ones (De Miguel et al 2014). In the T. magnatum natural habitats, the most abundant fungal species belong to Thelephoraceae, followed by Sebacinaceae, Inocybaceae, and Russulaceae (Murat et al 2005; Leonardi et al 2013).…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial community structures have been found to differ between natural and cultivated truffle habitats, between productive and nonproductive plantations, and between different Tuber species and developmental stages of truffles. Belfiori et al (2012) found that the diversity of ectomycorrhizal species is lower in cultivated plantations than in natural habitats, higher in Tuber brumale -colonized plants than that of T. melanosporum -colonized plants (Belfiori et al 2012), and higher in productive plantations than in the nonproductive ones (De Miguel et al 2014). In the T. magnatum natural habitats, the most abundant fungal species belong to Thelephoraceae, followed by Sebacinaceae, Inocybaceae, and Russulaceae (Murat et al 2005; Leonardi et al 2013).…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 99%
“…In the T. magnatum natural habitats, the most abundant fungal species belong to Thelephoraceae, followed by Sebacinaceae, Inocybaceae, and Russulaceae (Murat et al 2005; Leonardi et al 2013). In fact, Thelephoraceae are frequently found in mature truffle orchards, but the Hebeloma, Laccaria, and Russula species seem to associate with unproductive grounds (De Miguel et al 2014). Additionally, Barbieri et al (2007) found that the total bacteria count associated with T. magnatum decreases during the maturation of ascocarps and that α-Proteobacteria is the major bacterial group associated with T. magnatum ascomata.…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 99%
“…However, the role of these species in black truffle fruiting is still unknown nowadays. Several works (De Román and De Miguel, 2001;Reyna et al, 2006;Rubini et al, 2011;De Miguel et al, 2014) report the frequent identification of these species in truffle plantations, but they still have not been related to the life cycle of T. melanosporum.…”
Section: Damages Identified In the Tree Root Systemmentioning
confidence: 99%
“…Yet, we lack a comprehensive understanding of ECM fungal dynamics in natural truffle sites and plantations. In this context, De Miguel et al (2014) synthesize findings from 85 papers on truffle fungal communities around the world and provide insight on commonly occurring and likely competing ECM fungal species and on the influence of plantation age, host species, surrounding environment, and management practices on species composition. A new understanding of potential fungal species indicators of productive and nonproductive plantations emerges from this study.…”
Section: Purpose and Content Of This Special Issuementioning
confidence: 99%
“…Yet, we lack a comprehensive understanding of ECM fungal dynamics in natural truffle sites and plantations. In this context, De Miguel et al (2014) synthesize findings from 85 papers on truffle fungal communities around the world B. Águeda …”
mentioning
confidence: 99%